Diversity of Fagaceae on Hainan Island of South China During the Middle Eocene: Implications for Phytogeography and Paleoecology - Liu, Xiaoyan; Song, Hanzhang; Jin, Jianhua (Frontiers in Ecology and Evolution, 2020)
The Fagaceae family is currently widespread throughout tropical and temperate regions of South America and the Northern Hemisphere, especially East Asia, and has likely been so since the Eocene, according to fossil records. In China, Fagaceae fossils are rare in the lowest latitudes of South China. Here, we describe 12 species in 5 genera of Fagaceae (i.e. Berryophyllum, Castaneophyllum, Quercus, Castanopsis and Lithocarpus) based on leaf morphology and trichomes. These fossils are recovered from the Changchang Formation of Changchang Basin, Hainan Island, South China, indicating that Fagaceae has been distributed in these tropical low latitudes since the Eocene. Given that our fossils are closely related to the tropical and subtropical extant species, we speculate that Fagaceae lineages have likely diverged since the Eocene and that each extant lineage, such as Quercus sect. Cyclobalanopsis, became highly differentiated no later than middle Eocene. Based on the current living conditions of the extant species, we further speculate that the climate of Hainan Island was warm and wet during the middle Eocene, suitable for the growth and differentiation of the family.